2011
DOI: 10.2355/isijinternational.51.1072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Reduction Behavior of Mill Scale

Abstract: This paper presents an initial part of a project devoted to the recycling of mill scale in the form of selfreducing briquettes. First chemical and morphological characteristics of mill scale were investigated and next its gaseous reduction behavior was studied by thermogravimetry. The chemical characterization showed that wustite is the major constituent of this waste matter, with small amounts of magnetite, hematite and metallic iron. The microscopic examination of the scale revealed its complex and layered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 27 publications
3
40
0
3
Order By: Relevance
“…The activation energy of the fine iron oxide reduction by CO reported by Moon and Sahajwalla varie from 36 to 75 kJ/mol. 14) Fortini and Fruehan 17) estimate the activation energy of wustite reduction by CO as high as 168 kJ/mol which is a bit higher then upper limit of the 60-150 kJ/mol range given by Coetze et al 19) In our previous work 3) on the reduction of the scale by CO, the activation energy of reaction rate constant was found to be about 80 kJ/mol. It was also observed that the gaseous reduction of scale occurs according to the shrinking core model under chemical control, i.e.…”
Section: Limiting Reaction Stepmentioning
confidence: 71%
See 4 more Smart Citations
“…The activation energy of the fine iron oxide reduction by CO reported by Moon and Sahajwalla varie from 36 to 75 kJ/mol. 14) Fortini and Fruehan 17) estimate the activation energy of wustite reduction by CO as high as 168 kJ/mol which is a bit higher then upper limit of the 60-150 kJ/mol range given by Coetze et al 19) In our previous work 3) on the reduction of the scale by CO, the activation energy of reaction rate constant was found to be about 80 kJ/mol. It was also observed that the gaseous reduction of scale occurs according to the shrinking core model under chemical control, i.e.…”
Section: Limiting Reaction Stepmentioning
confidence: 71%
“…In fact, in our earlier study 3) on gaseous reduction of scale, two different morphologies of iron were observed: the porous iron, which prevailed in the samples reduced at higher temperatures (1 100°C and 1 200°C), and the iron whiskers formed in the scale samples reduced at lower temperatures (900°C and 1 000°C). It was thus interesting to examine and compare the morphology of iron produced with different solid carbonaceous materials, in order to identify the conditions in which the self-reducing reactions occur.…”
Section: Morphology Of Reduced Ironmentioning
confidence: 78%
See 3 more Smart Citations